1997
DOI: 10.1093/ajcp/107.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Proliferative Activity of Ovarian Carcinoma as Revealed by PCNA and AgNOR Analyses

Abstract: Proliferative activity of a malignant tumor is known to reflect its biologic aggressiveness. Proliferating cell nuclear antigen (PCNA) is a marker of cellular proliferation, and silver-stained nucleolar organizer regions (AgNORs) have been shown to correlate with ploidy and proliferative activity of cells depending on the method of assessment; the mean number of AgNORs per nucleus reflects ploidy, whereas the mean percentage of nuclei with five or more AgNORs per nucleus indicates proliferative activity. In ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…Many studies have shown that the growth rate differs markedly among tumors [1, 2, 3], and that it closely correlates with prognosis [1, 2, 3, 4]. Hence, it is unclear which factors contribute most to the heterogeneity in the growth potential among tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the growth rate differs markedly among tumors [1, 2, 3], and that it closely correlates with prognosis [1, 2, 3, 4]. Hence, it is unclear which factors contribute most to the heterogeneity in the growth potential among tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also noted a lack of correlation between these indices when analyzed separately in other kinds of tumors (28)(29)(30)(31)(32) .The inadequacy of statistical correlations between the PCNA index and AgNOR counts has been attributed to the fact that these methods quantify different aspects of proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…But less studies finding a significant relationship between the decrease in the mAgNOR post-therapy with stage. (13,23,24) Chemoradiotherapy is a chemotherapy combined with radiotherapy concurrently used to control tumor lokoregional and improve the survival of patients in order to overcome cancer cells systemically through microcirculation. In this study most of the samples will undergo neoadjuvant chemotherapy intended to reduce the size of the tumor before radiotherapy.…”
Section: Acknowledgementmentioning
confidence: 99%